2015
DOI: 10.1108/nlw-06-2014-0073
|View full text |Cite
|
Sign up to set email alerts
|

The information practices of Business PhD students

Abstract: The aim of this study was to investigate how PhD students discover, choose and use information and literature for their research. Design/methodology/Approach: Eight PhD students at the Norwegian Business School (BI) were interviewed. The interviews were based on a phenomenological approach. Findings: The use of both library databases and Google Scholar is frequent and contextual. The informants ranked the library databases as more useful than Google Scholar. Methods for keeping up to date varied and were conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 19 publications
0
11
0
3
Order By: Relevance
“…With regard to searching, it is reported in Catalano (2013) that doctoral students in the social sciences make more use of library resources than in other disciplines, to the exception of business and economics graduate students who seem to favour Internet resources. Bøyum and Aabø (2015) have, however, found in their small case study at the Norwegian Business School that this is not necessarily true. Indeed, the authors found that doctoral students reported using both library resources and Google Scholar, but found library databases more useful for their research.…”
Section: Disciplinary Similarities and Differencesmentioning
confidence: 91%
See 2 more Smart Citations
“…With regard to searching, it is reported in Catalano (2013) that doctoral students in the social sciences make more use of library resources than in other disciplines, to the exception of business and economics graduate students who seem to favour Internet resources. Bøyum and Aabø (2015) have, however, found in their small case study at the Norwegian Business School that this is not necessarily true. Indeed, the authors found that doctoral students reported using both library resources and Google Scholar, but found library databases more useful for their research.…”
Section: Disciplinary Similarities and Differencesmentioning
confidence: 91%
“…There is good evidence in the literature that, overall, doctoral students' selfreported perceptions of their own capabilities indicate that they are satisfied with their own information-seeking skills (Bøyum andAabø 2015, Fleming-May andYuro 2009;, although when looked at closely their practice seems to be telling a different story altogether. Search strategies are by definition an iteration process.…”
Section: From Initial Search To Constructing Search Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Bibliotekarene har innsikt i, forstår og anerkjenner disiplinens eller underdisiplinenes ulike informasjonspraksiser (se f.eks. Bøyum & Aabø, 2015;Jamali & Nicholas, 2008). Bibliotekarene kan oppleves som relevante diskusjonspartnere for studenter med samme faglige bakgrunn.…”
Section: : Problemformulerende Tilnaermingunclassified
“…Percebe-se, na literatura sobre a temática (BØYUM; AABØ, 2015;COIMBRA, 2008;ISAH, 2009;NUNES, 2014;OLIPHANT, 2010), a prevalência de análises qualitativas, geralmente a partir da criação de categorias.…”
unclassified